2019
DOI: 10.5530/ijpi.2019.2.19
|View full text |Cite
|
Sign up to set email alerts
|

Rhodiola rosea: A Quantitative and Qualitative Assessment of Global Publications Output during 2003-18

Abstract: A quantitative and qualitative assessment of global research output (2016) on the "Rhodiola rosea" plant based on select bibliometric indicators, using Scopus database covering period 1993-2018, is presented here. Analyzed data on a series of bibliometric measures, like average annual growth, citations per paper, international collaborative papers, relative citation index, activity index, top productive countries, organizations, authors, journals and highly cited papers. The global publications registered an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…This plant is one of the most important adaptogens. The number of scientific publications about this plant has been growing recently [12].…”
Section: Introductionmentioning
confidence: 99%
“…This plant is one of the most important adaptogens. The number of scientific publications about this plant has been growing recently [12].…”
Section: Introductionmentioning
confidence: 99%
“…The names of important organizations, researchers and companies were also identified. Similar bibliometric studies have been carried out on other medicinal plants, such as Aegle marmelos, 9 Aloe vera, 10 Andrographis paniculata, 11 Azadrachta indica, 12 Curcuma longa, 13 Glycyrrhiza glabre, 14 Nigella sativa, 15 Ocimum sanctum, 16 Phyllanthis emblica, 17 Rhodiola rosea, 18 Tinospora cordifolia 19 and Withania somnifera. 20 Since India is the largest contributor to global Moringa oleifera research and as yet no bibliometric study has been published on the bibliometric assessment of India's research in this area, as a result we felt the need to undertake the present study.…”
Section: Literature Reviewmentioning
confidence: 57%
“…Many researchers have also explored studies relevant to medicinal plants. [3][4][5][6][7][8][9][10][11][12][13][14] This study identified India's contribution in international collaboration documents at the national level and key partners in international collaboration, further analyzing the characteristics of institutions, authors, frequently cited articles, etc.…”
Section: Related Studiesmentioning
confidence: 99%